EFEK LARVASIDA EKSTRAK ETANOL DAUN PEPAYA (Carica papaya) TERHADAP LARVA Aedes aegypti - Meidy Shadana; Suri Dwi Lesmana; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Dengue Hemorrhagic Fever (DHF) is a dangerous viral disease because itcan cause death in a very short time. The desease is caused by dengue viral withAedes aegypti (Ae.aegypti) as the main vector. Various ways have been made toeradicate Ae.aegypti, one of which is the use of chemical larvicides. However, theuse of this chemical larvicides has adverse effects, so it is necessary to findanother alternative such using botanical larvicides. Papaya (Carica papaya) is aplant that is potentially as botanical larvicides. The aim of this research is toknow the larvicide effect etanol extract of papaya leaf (Carica papaya) againtsAe.aegypti larvae. This is an experimental research by using variousconcentration are 400ppm, 800ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm,1800ppm and a container of distilled water as a control. Test performed threerepetitions with each concentration contains of 20 larvae. The level of larvaemortality was observed after 24 hours. Analysis of the research results usingProbit regression analysis obtained LC50 945.165ppm and LC90 1495.219ppm.Keywords: Larvicide effect, Carica papaya, Aedes aegypti